Answer:
One Solution
Step-by-step explanation:
x + 3y = 3
x - y = -3
4y = 6 Subtract to solve by elimination.
y =
Divide by 4.
x -
= -3 Substitute
for y in the original equation.
x = -
Add
.
Answer:
<h2>x=2</h2><h2>y=4</h2>
Step-by-step explanation:
5x-y=6
2x+y=8
add them up
7x=14
divide by 7 to get x
x=2
fit it into both equation
y=4
TE/4 =U
Step by step
You multiply both sides by E to get rid of it then you have TE =4U and then u divide it by 4 and get TE/4 =U
Answer:
It is actually A
Step-by-step explanation:
1. E
2.D
3.G
4.E
5.N
6.U
7.I
8.T
10.Y